Maternal exposure to genistein during pregnancy and oxidative DNA damage in testes of male mouse offspring - Godschalk, Roger W. L.; Janssen, Margit C. M.; Vanhees, Kimberly; Doorn-Khosrovani, Sahar Barjesteh van Waalwijk van; Schooten, Frederik-Jan van (Frontiers in Nutrition, 2022)
Background: Genistein is a dietary supplement with phyto-estrogenic properties. Therefore, high intake of genistein during pregnancy may have adverse effects on the genetic integrity of testes and germ cells of male offspring. In this study, we examined whether maternal exposure to genistein during pregnancy induced oxidative DNA damage in the male germline at adolescence. Methods: Atm-∆SRI mice have lower glucose-6-phosphate dehydrogenase (G6PDH) activity, which is important for maintaining levels of reduced glutathione and therefore these mice have an increased susceptibility to oxidative stress. Parental heterozygous Atm-∆SRI mice received a genistein-rich or control diet, after which they were mated to obtain offspring. During pregnancy, mothers remained on the respective diets and after delivery all animals received control diets. Redox status and oxidative DNA damage were assessed in testes and sperm of 12 weeks old male offspring. Gene expression of Cyp1b1, Comt, and Nqo1 was assessed in testes, and DNA methylation as possible mechanism for transmission of effects to later life. Results: Intake of genistein during pregnancy increased oxidative DNA damage in testes of offspring, especially in heterozygous Atm-∆SRI mice. These increased DNA damage levels coincided with decreased expression of Comt and Nqo1. Heterozygous Atm-∆SRI mice had higher levels of DNA strand breaks in sperm compared to wild type littermates, and DNA damage was further enhanced by a genistein-rich maternal diet. G6PDH activity was higher in mice with high maternal intake of genistein compared to control diets, suggesting compensation against oxidative stress. A positive correlation was observed between the levels of DNA methylation and oxidative DNA damage in testes. Conclusion: These data indicate that prenatal exposure to genistein altered gene expression and increased DNA damage in testes and sperm of adolescent male offspring. These effects of genistein on DNA damage in later life coincided with alterations in DNA methylation.